Comparative relationship in perceptual element in triggering emotional value of Malaysian car design / Muhamad Aiman Afiq Mohd Noor and Azhari Md Hashim - Mohd Noor, Muhamad Aiman Afiq; Md Hashim, Azhari (Universiti Teknologi MARA, Kedah, 2020)
Automotive industry in Malaysia transforming the landscape from an agricultural to industrial nation, risen the high-value economic activities and improved the standard of living for most of the sector. As this sector continues to advance, more highvalue jobs will be available and these include production engineers, modeler as well stylist, product, process and tool designers. Innovative design development in car segment, exterior and interior design, trend and advances technology creates new car model to attract consumer purchasing and compete among manufacturer. New car model will evoke consumer emotion which underlying the human values and these values can be useful for predicting the emotional responses to this new design. Thus, this paper aims to compare the relationship arise in triggering emotional value between Malaysian car design namely Proton and Perodua in literature findings of methods. The history of these two manufacturers and its competitors were elaborate and methods available in searching for this element were discussed and propose as future recommendation as further study.